Вербалізація образного складника концепту FREUNDSCHAFT/ ДРУЖБА у німецькому художньому тексті - Дягілєва, Жаннета; Dyagilyeva, Zhanetta (Східноєвропейський національний університет імені Лесі Українки, 2013)
У цій статті досліджено засоби вербалізації образного складника концепту FREUNDSCHAFT/ДРУЖБА в німецькому художньому тексті. Описано особливості художнього тексту як вторинної моделювальної системи,розглянуто найпродуктивніші типи семантичного переносу для вербалізації образу дружби.This article focuses on the means of verbalization of a figurative component of the concept FREUNDSCHAFT/ FRIENDSHIP in German fiction. The features of the fiction as secondary modeling system are described. Owing to the singled out metaphorical images the semantic structure of the concept in question is specified and representations of native speaker of German about value of friendship, its ontological connection with love and stages of development of friendly relations are defined. The metaphorical epithet with positive emotional-evaluating connotation which confirms presence of friendship in the system of cultural values of German people is separately considered. The most productive types of semantic transfer for verbalization of the image of friendship are allocated: anthropomorphous, biomorphous, reimorphous and spatial metaphor. The destruction of indissoluble unity of the person and his relations in the metaphorical image of the friendship is ascertained.
Verbalization of a Figurative Component of the Concept Freundschaft/ Friendship in German Fiction
Keywords: концепт; образний складник; художній текст; метафора; тип семантичного переносу; concept; figurative component; fiction; metaphor; type of semantic transfer